Nutritional profile and oxidative stress in adolescent soccer players - Guissoni, F. M.; Deminice, R.; Payão Ovidio, P.; Zangiacomi Martinez, E.; Afonso Jordao, A.; Mialich, M. S. (Central European Journal of Sport Sciences and Medicine, 2020)
High-intensity exercise increases reactive oxygen species formation, which in excess may cause oxidative stress. We assessed nutritional status and exercise-induced oxidative stress in 20 adolescent male soccer players (age: 15-17). Participants were divided into two teams for a 60-minute friendly match and evaluated immediately before (Pre-match), 30 minutes after (Post-match I) and 24 hours after (Post-match II) the game. All players recorded a 3-day dietary intake. Biochemical tests were performed for lipid profile, muscle damage (creatinine and creatinine kinase [CK]) and oxidative stress (thiobarbituric acid-reactive substances [TBARS], protein carbonyls [PC], reduced glutathione [GSH], and vitamins E, C, and A). CK and creatinine were significantly elevated at Post-match I (p < 0.01), returning to baseline at Post-match II. Vitamins E, C and A were significantly elevated at Post-match I (p < 0.01), but only vitamins E and A remained high at Post-match II. TBARS showed no significant changes. GSH showed a significant decrease (p < 0.01) and PC showed a slight but significant increase (p < 0.01) at Post-match II. The recruitment of non-enzymatic antioxidants prevented lipid peroxidation, but dietary and especially endogenous defence responses were insufficient to prevent protein oxidation. Proper nutrition is essential to improve the activity of the antioxidant defence system, preventing exercise-induced oxidative stress.